Investigating bisubstrate inhibitors of PRMT1 and CARM1 - Gunnell, Emma (2019)
Protein arginine methyltransferases (PRMTs) are gaining traction as a novel drug target class for a wide range of diseases. The high sequence conservation within the active sites of the nine human PRMTs, particularly in the co-factor (S-adenosyl methionine [SAM]) binding site, makes the design of isozymeselective PRMT inhibitors challenging. Linking guanidine or substrate peptides to SAM mimics has shown potential as an approach to designing isozymeselective inhibitors, but the peptidic nature of such compounds limits their in vivo utility. Herein, the binding of a novel series of non-peptidic bisubstrate inhibitors to CARM1 and PRMT1 was evaluated.